2006
DOI: 10.1088/0957-0233/17/3/s10
|View full text |Cite
|
Sign up to set email alerts
|

Real-time atomic encoder using scanning tunnelling microscope and regular crystalline surface

Abstract: In this paper, we demonstrate a technique for highly stable atom-tracking control of a scanning tunnelling microscope (STM) tip by referring to an atomic point on a regular crystalline surface. We also demonstrate an atomic encoder using ‘atom-by-atom’ step control along a crystalline axis. A graphite crystal, whose lattice spacing is approximately 0.25 nm, was utilized as the reference material. To enhance the stability of the atom-tracking control in the presence of external disturbances, a robust controller… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Therefore, the two unit lattice vectors of the HOPG crystal can be used, in combination with an STM, as two-dimensional references (or standards) with sub-nanometre resolution or less [7][8][9]. The authors have previously demonstrated atomstep control along the a 1 or a 2 direction on the HOPG crystalline surface over a range of 200 atoms using STM [10]. By this method, counting the unit lattice vector a 1 or a 2 introduces a displacement measurement along the a 1 or a 2 direction, and serial counting of the unit lattice vectors a 1 and a 2 allows for two-dimensional displacement measurement [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the two unit lattice vectors of the HOPG crystal can be used, in combination with an STM, as two-dimensional references (or standards) with sub-nanometre resolution or less [7][8][9]. The authors have previously demonstrated atomstep control along the a 1 or a 2 direction on the HOPG crystalline surface over a range of 200 atoms using STM [10]. By this method, counting the unit lattice vector a 1 or a 2 introduces a displacement measurement along the a 1 or a 2 direction, and serial counting of the unit lattice vectors a 1 and a 2 allows for two-dimensional displacement measurement [10].…”
Section: Introductionmentioning
confidence: 99%
“…The authors have previously demonstrated atomstep control along the a 1 or a 2 direction on the HOPG crystalline surface over a range of 200 atoms using STM [10]. By this method, counting the unit lattice vector a 1 or a 2 introduces a displacement measurement along the a 1 or a 2 direction, and serial counting of the unit lattice vectors a 1 and a 2 allows for two-dimensional displacement measurement [10]. However, it is impossible to realize simultaneous two-dimensional displacement measurement in arbitrary directions.…”
Section: Introductionmentioning
confidence: 99%